2022
DOI: 10.1007/s11332-022-00966-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise rehabilitation on COVID-19 outcomes: a systematic review of observational and intervention studies

Abstract: Purpose Disturbance to physical and psychological characteristics among COVID-19 survivors are not uncommon complications. In the current systematic review, we aimed to investigate the role of exercise rehabilitation programs, either in acute or post-acute phase, on COVID-19 patients’ outcomes. Methods A systematic search was conducted in November 2021 of Web of Sciences, PubMed-Medline, Google Scholar, and Scopus. Observational and intervention studies on COVID-19-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
0
15
0
8
Order By: Relevance
“…To our knowledge, this is the first clinical study of patients with COVID-19 sequelae followed for 8 weeks to investigate the effects of physical exercise on physical and cognitive performance in this population. A recent systematic review 24 showed that nine observational studies (n=957) and 14 intervention studies (n=469) on rehabilitation in subjects with COVID-19 had been published. In most studies, rehabilitation was carried out during hospitalization and the acute phase of the disease (within the first 4 weeks after the onset of symptoms), or in the post-acute phase (after 4 weeks of the onset of symptoms) lasting 1 42 , 4 43 , and 6 weeks 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, this is the first clinical study of patients with COVID-19 sequelae followed for 8 weeks to investigate the effects of physical exercise on physical and cognitive performance in this population. A recent systematic review 24 showed that nine observational studies (n=957) and 14 intervention studies (n=469) on rehabilitation in subjects with COVID-19 had been published. In most studies, rehabilitation was carried out during hospitalization and the acute phase of the disease (within the first 4 weeks after the onset of symptoms), or in the post-acute phase (after 4 weeks of the onset of symptoms) lasting 1 42 , 4 43 , and 6 weeks 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of rehabilitation in treating patients with persistent symptoms of COVID-19 have not been fully elucidated 24 . In addition, evidence has shown an effect on physical function in elderly 25 or hospitalized subjects 24,26,27 , with few references to cognitive aspects 28 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another 6-week aerobic and strength exercise rehabilitation study for critically ill COVID-19 survivors reduced dyspnea and increased exercise capacity were observed for the rehabilitation group (n = 13; 57.6 ± 10.1 years) and for the control group (n = 13; 56.8 ± 8.7 years), which did not exercise 27 .The effects of rehabilitation in treating patients with persistent symptoms of COVID-19 have not been fully elucidated 24 . In addition, evidence has shown an effect on physical function in elderly 25 or hospitalized subjects 24,26,27 , with few references to cognitive aspects 28 . In this sense, the present study aimed to evaluate the effects of a face-to-face physical exercise rehabilitation program in patients with persistent symptoms of COVID-19 on fatigue and dyspnea, exercise capacity, pulmonary function, functional status, cognitive function, symptoms of anxiety and depression, and peripheral muscle strength.…”
mentioning
confidence: 99%